Investigation of the effects of plasma arc parameters on the machining of different engineering materials - Mohd Hafidz Norizaman (School of Manufacturing Engineering, 2012)
The objectives of the study are to determine the optimum parameters which affect the manual plasma arc cutting in terms of surface roughness (SR) and material removal rate (MRR); to study the relation between the output of surface roughness (SR) and material removal rate (MRR) and to study the behaviour of the material based on hardness values near heat affected zone area, transition zone area, and unaffected heat zone area.